1998
DOI: 10.1023/a:1008002905588
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The complete nucleotide sequence of human papillomavirus type 67 (HPV 67) cloned from a vaginal intraepithelial neoplasia, has been determined. It consists of 7801 nucleotides with a GC content of 38.4% and exhibits similar genome organizations of genital HPVs. By phylogenetic analysis based on the full nucleotide sequences of E6 open reading frame of 28 genital HPVs, HPV 67 was clustered with HPV 16, 31, 33, 34, 35, 52, and 58.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Samples with these HPV types, except HPV70 (low-risk for cancer), were also included in this study. HPV26 is a potential HR-type [ 15 ] as well as HPV67 [ 16 ]. In one study, HPV82 was classified as an HR-type [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Samples with these HPV types, except HPV70 (low-risk for cancer), were also included in this study. HPV26 is a potential HR-type [ 15 ] as well as HPV67 [ 16 ]. In one study, HPV82 was classified as an HR-type [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…This observation is logical since genotypes 67 and 97 are subtypes of HPV 16 and HPV 18, which are known to have oncogenic potential. Some authors have isolated these genotypes from high-grade intraepithelial lesions (12,13).…”
Section: Alphapapillomavirus Genus In Host Cells Preliminary Results ...mentioning
confidence: 99%
“…The results revealed that almost all of the sequenced HPV67 genomes from Japan belonged to lineage A (11/12, 91.7%), suggesting a high prevalence of HPV67 lineage A variants in Japan. The reference genome of sublineage A1 (D21208) [ 15 ] was also isolated from a Japanese woman with vaginal intraepithelial neoplasia [ 4 ]. In contrast, a recent study that used NGS for detection of multiple HPV types reported on 12 complete genome sequences of HPV67, which showed that HPV67 variant distribution in Luxembourg was totally biased toward lineage B [ 16 ], which was confirmed by our phylogenetic analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%